Human Resources Management Practices and Employees Retention in Competitive Business Environments - Olatoye, Adeolu Oludare; Bukki, Abolaji Olugbenga; Ojeyinka, Aderonke Grace (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2025)
The study examined human resources management practices and employees retention in competitive business environments in Ogun State. Four research questions and two hypotheses were raised and tested. A descriptive survey design with a sample of 300 staff was purposively selected from six business organisations. Self-constructed instrument titled Human Resources Management Practices and Retaining Employees Questionnaire was used to collect data and analysed using regression analysis. Findings revealed that job security, on-the-job training, promotion and compensation directly influence retaining employees. The study recommended among others that management should make sure that the promotion of deserving employees is quickly done and they should always implement proactive human resource management strategies based on emerging requirements.